2014
DOI: 10.1074/jbc.m113.529131
|View full text |Cite
|
Sign up to set email alerts
|

Novel Structural Features in Candida albicans Hyphal Glucan Provide a Basis for Differential Innate Immune Recognition of Hyphae Versus Yeast

Abstract: Background:The human innate immune system can discriminate between Candida albicans yeast and hyphal forms. Results: C. albicans hyphae possess glucan structures that are unique to the hyphae and are not found in yeast. Conclusion: Hyphal glucan elicits robust immune responses.Significance: These data provide a structural basis for differential immune recognition of C. albicans yeast versus hyphae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 64 publications
4
115
1
3
Order By: Relevance
“…These polysaccharides induce protective responses during infection (61,62). Most of the biological studies on the effects of glucans have focused on ␤-1,3-glucans (28,(63)(64)(65)(66)(67). In agreement with these data, the increase of ␤-1,3-glucans in AmB-resistant strains correlates with the enhanced response of PBMCs exposed to these isolates.…”
Section: Discussionsupporting
confidence: 74%
“…These polysaccharides induce protective responses during infection (61,62). Most of the biological studies on the effects of glucans have focused on ␤-1,3-glucans (28,(63)(64)(65)(66)(67). In agreement with these data, the increase of ␤-1,3-glucans in AmB-resistant strains correlates with the enhanced response of PBMCs exposed to these isolates.…”
Section: Discussionsupporting
confidence: 74%
“…The relevance of these findings to fungal infection was confirmed by showing that the disappearance of CHOP proteins was produced by Candida in parallel with the formation of hyphae and the attendant exposure of ␤-glucans on budding yeasts. Since it has recently been disclosed that a unique close-chain chemical structure of hyphal ␤-glucans induce a robust production of proinflammatory responses (35), it is possible that the presence of cyclical ␤-glucans might explain the different effects of yeast and hyphal Candida on nuclear CHOP. These findings might have two relevant consequences.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that changes in the cell wall organization also influence the interaction of C. albicans with immune effector mechanisms. Cell wall components are major microbe-associated molecular patterns (MAMPs), which are recognized by a range of pattern recognition receptors (PRRs) on host cells triggering antimicrobial mechanisms and the release of cytokines/chemokines that modulate the resulting immune response Lowman et al, 2014;Netea et al, 2006). Alteration of the cell wall architecture will therefore ultimately lead to altered recognition responses, and indeed it has been shown that, for example, the growth of C. albicans on lactate stimulates the production of an anti-inflammatory IL-10 rather than proinflammatory IL-17 response by human peripheral blood mononuclear cells (PBMCs) (Ene, Cheng, Netea, & Brown, 2013).…”
Section: Metabolic Adaptationdnutrient and Micronutrient Acquisition mentioning
confidence: 99%